HIDROPNEUMOTHORAKS ET CAUSA TB PARU - Dinda An-nisa; Puspa Rosfadilla (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Hydropneumothorax is a condition where there is air and fluid in the pleural cavity resulting in the collapse of lung tissue. The exact incidence is unknown but it is found that the incidence of pneumothorax ranges from 2.4 to 17.8/100,000 population per year. In this case, a 42-year-old man with complaints of chest pain since 2 weeks before admission to the hospital. The complaints included shortness of breath and continuous coughing. From the examination results obtained BP 120/80, HR: 135x/I, RR: 18 x/I, and temperature: 37oC. Physical examination found asymmetrical chest movements, chest tube in the sinistra thorax, weak vocal fremitus in the basal part of the left hemithorax at the level of posterior ICS XI, hypersonor in the right lung at the level of ICS II-IV and dimmed in the left basal part at the level of ICS V and a decrease in left lung breath sounds. X-ray examination showed an area of lusensi without pulmonary scars in the lateral aspect of the sinistral hemithorax with a ridge in the basal aspect of the sinistral hemithorax accompanied by an air fluid level in the left hemithorax. The patient was diagnosed with hydropneumothorax ec pulmonary tuberculosis with water seal drainage.